2013
DOI: 10.1016/j.biomaterials.2013.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Porous chitosan-hyaluronic acid scaffolds as a mimic of glioblastoma microenvironment ECM

Abstract: Cancer therapeutics are developed through extensive screening; however, many therapeutics evaluated with 2D in vitro cultures during pre-clinical trials suffer from lower efficacy in patients. Replicating the in vivo tumor microenvironment in vitro with three-dimensional (3D) porous scaffolds offers the possibility of generating more predictive pre-clinical models to enhance cancer treatment efficacy. We developed a chitosan and hyaluronic acid (HA) polyelectrolyte complex 3D porous scaffold and evaluated its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
151
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 196 publications
(161 citation statements)
references
References 65 publications
10
151
0
Order By: Relevance
“…Among the ECM components, an important role has been demonstrated for HA, able to regulate the glioma cell phenotype [231] or to increase stem-like properties of glioblastoma cells [232]. For this reason, hydrogels containing HA have been proposed as a scaffold for neuronal tumors [233].…”
Section: D Tumoral Cns Cultures On Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the ECM components, an important role has been demonstrated for HA, able to regulate the glioma cell phenotype [231] or to increase stem-like properties of glioblastoma cells [232]. For this reason, hydrogels containing HA have been proposed as a scaffold for neuronal tumors [233].…”
Section: D Tumoral Cns Cultures On Scaffoldsmentioning
confidence: 99%
“…Moreover, several other matrix compositions have been tested with the aim of better reproducing the in vivo microenvironment. Thus, invasion assays have been performed in HA-based hydrogel [230,[233][234][235]]. …”
Section: D Models For Testing Motility/invasion Of Cns Tumorsmentioning
confidence: 99%
“…to promote CD133 overexpression, making it useful for the study of glioma CSCs. 53 Porous HA-chitosan scaffolds have also been used to culture multicellular spheroids composed of glioblastoma 54 and non-small cell lung cancer cells, 55 noting increased spheroid formation, stem-like properties, and invasiveness in both cases. Additionally, non-small cell lung cancer cells revealed more EMT markers as well as exhibited 5-6 times higher resistance to cisplatin and 16-56 times higher resistance to methotrexate compared to conventional 2D cultures.…”
Section: Biomaterials For Csc Growthmentioning
confidence: 99%
“…Primary cells from glioma patient tumor material exposed to increasing concentrations of HA responded with rounded morphology and reduced migration, suggesting that HA concentrations may affect glioma cell behavior. [62] Consistently, addition of HA to porous chitosan scaffolds [63] or to artificial hydrogels [64] increased the expression of stem cell markers and VEGF and HIF-1, respectively. However, the finding that increasing matrix stiffness -by adding agarose to a collagen I matrix -blocks glioma invasiveness, [19] suggested that stiffness alone and independent of ligand binding acted as a critical determinant for primary brain tumor cell function.…”
Section: The Impact Of the Embedding Matrix On The Behavior Of The Tumentioning
confidence: 68%